A Novel Prospective Study Assessing the Combination of Photodynamic Therapy and Proton Radiation Therapy: Safety and Outcomes When Treating Malignant Pleural Mesothelioma1. (28th December 2018) - Rice, Stephanie R.; Li, Yun R.; Busch, Theresa M.; Kim, Michele M.; McNulty, Sally; Dimofte, Andrea; Zhu, Timothy C.; Cengel, Keith A.; Simone, Charles B.
Abstract: Malignant pleural mesothelioma remains difficult to treat, with high failure rates despite optimal therapy. We present a novel prospective trial combining proton therapy (PT) and photodynamic therapy (PDT) and the largest‐ever mesothelioma PT experience ( n = 10). PDT photosensitizers included porfimer sodium (2 mg·kg −1 ; 24 h drug‐light interval) or 2‐[1‐hexyloxyethyl]‐2‐devinyl pyropheophorbide‐a (HPPH) (4 mg·m −2 ;48 h) with wavelengths of 630 nm to 60J·cm −2 and 665 nm to 15‐45J·cm −2, respectively. With a median age of 69 years, patients were predominantly male (90%) with epithelioid histology (100%) and stage III‐IV disease (100%). PT was delivered to a median of 55.0 CGE/1.8‐2.0 CGE (range 50–75 CGE) adjuvantly ( n = 8) or as salvage therapy ( n = 2) following extended pleurectomy/decortication (ePD)/PDT. Two‐year local control was 90%, with distant and regional failure rates of 50% and 30%, respectively. All patients received chemotherapy, and four received immunotherapy. Surgical complications included atrial fibrillation ( n = 3), pneumonia ( n = 2), and deep vein thrombosis ( n = 2). Median survival from PT completion was 19.5 months (30.3 months from diagnosis), and 1‐ and 2‐year survival rates were 58% and 29%. No patient experienced CTCAEv4 grade ≥2 acute or late toxicity. Our prolonged survival in very advanced‐stage patients compares favorably to survival for PT without PDT and photon therapy with PDT, suggesting possible spatial or systemic cooperativity and immune effect. Abstract : Malignant pleural mesothelioma (MPM) remains difficult to treat, with high failure rates despite optimal therapy. We present a novel trial combining proton therapy (PT) and photodynamic therapy (PDT) with porfimer sodium or 2‐[1‐hexyloxyethyl]‐2‐devinyl pyropheophorbide‐a in Stage III‐IV MPM. All patients received chemotherapy, and four received immunotherapy. Two‐year local control was 90%, with distant and regional failure rates of 50% and 30%, respectively. Median survival from PT completion was 19.5 months, and 1‐ and 2‐year survival rates were 58% and 29%. Our prolonged survival in very advanced‐stage patients compares favorably to survival for PT without PDT and photon therapy with PDT.